Inferior-Medial Dry Needling at the Thoracolumbar Junction: A Cadaveric Study - Christi L. Williams; Sue E. Curfman; Stacey R. Lindsley; Christian R. Falyar; Ryan C. McConnell (North American Sports Medicine Institute, 2024)
# Background Dry needling (DN) has emerged as a popular therapeutic intervention for managing musculoskeletal pain. While major adverse events are generally rare, those that have been reported in vulnerable areas such as the spine and thorax can be serious and warrant further investigation regarding safe techniques in and around these areas. # Purpose The purpose of this study was to reproduce the methods employed by Williams et al. but with an inferior-medial multifidus DN technique to determine if a dry needle can penetrate the ligamentum flavum (LF) and breach the spinal canal at the thoracolumbar junction. # Study Design Descriptive Cadaveric study. # Methods The procedure was performed on a cadaver in the prone position. The needle was advanced under ultrasound guidance to determine if a 0.30 x 40 mm dry needle inserted lateral to the spinous process of T12 and directed inferior-medially could penetrate the LF and enter the spinal canal. # Results A 0.30 x 40 mm dry needle inserted 1.9 cm lateral to the spinous process of T12 was able to traverse the space between the vertebral laminae of T12 and L1, penetrate the LF, and enter the spinal canal with an inferior-medial needle angulation of 33-degrees medial and 18-degrees inferior. # Conclusion The results of this study demonstrate the feasibility of a dry needle entering the spinal canal at the thoracolumbar junction using an inferior-medial technique. These findings support the potential role of ultrasound guidance in the training and clinical practice of DN, especially in regions where safety issues have been documented. # Level of Evidence Level IV.